8‐exo‐dig‐Selective Cycloisomerization for the Synthesis of Dibenzo[b, e][1, 4]diazocines Using Cationic AuI Catalysts. Issue 34 (23rd August 2018) - Ito, Mamoru; Inoue, Daisuke; Takaki, Asahi; Kanyiva, Kyalo Stephen; Shibata, Takanori
Abstract : The cationic Au I ‐catalyzed intramolecular reaction of N ‐propargyl‐2‐anilinoanilines gave a diazocine skeleton via 8‐ exo ‐ dig ‐selective cycloisomerization by the suppression of 6‐ endo ‐ dig cycloisomerization. Both terminal and internal alkynes could be used according to the choice of ligand of the Au I complex, and various dibenzo[ b, e ][1, 4]diazocines were obtained. Control experiments suggested that two nitrogen atoms in the tether of substrates were critical in this selective transformation. Abstract : The cationic Au I ‐catalyzed intramolecular reaction of N ‐propargyl‐2‐anilinoanilines gave a diazocine skeleton via 8‐ exo ‐ dig ‐selective cycloisomerization. Both terminal and internal alkynes could be used according to the choice of ligand of the Au I complex. Two nitrogen atoms in the tether of substrates were critical in this selective transformation.